Multi-objective optimization of closed-loop supply chains in uncertain environment - Ozkir, Vildan; Basligil, Huseyin (ELSEVIER SCI LTD, 2013)
This paper reveals the main features of establishing a closed loop supply chain (CLSC) including recovery processes. We examine the problem through product recovery chain regarding the consumer sourced product returns, end-of-use products and end-of-life products. After defining general CLSC network including customers, collection points, reverse centers, plants, recovery facilities and distribution centers, we propose a multiple objective optimization model regarding three recovery options; material recovery, component recovery and product recovery. In this context, we deduce three level goal formulations; maximizing satisfaction level of trade, maximizing satisfaction degrees of customers, and finally maximizing total CLSC profit function. The objective of the proposed model is to seek the optimal number and location(s) of these CLSC facilities and determine the optimal transportation quantities, production quantities, purchasing quantities. Ultimately, the model is applied to an illustrative case and concluding remarks are made regarding the results. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Closed-loop supply chain; Supply chain design; Sustainability; Product recovery; Fuzzy logic; Multi objective optimization; NONLINEAR MEMBERSHIP FUNCTIONS; GOAL PROGRAMMING-PROBLEMS; AUTOMOTIVE INDUSTRY; TOLERANCE APPROACH; FUZZY; MANAGEMENT; PERFORMANCE; NETWORKS; ALGORITHM; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology